The Coase theorem and idea of transaction costs – their significance for the development of economics - Godłów-Legiędź, Janina (Comparative Economic Research. Central and Eastern Europe, 2010)
Ronald Coase drew the attention of main stream economists to the significance of social coordination in the economic system. The key role was played here by much-disputed political conclusions drawn from Coase’s idea as well as by his famous theorem and the zero transaction costs theory. The study focuses on the division of labor as a starting point for analysis of zero transaction costs. From this vantage point, the best example of the world of zero transaction costs is Robinson Crusoe’s island. However, very often the concept of zero transaction costs is associated with the assumption of perfect information. If we stretch this assumption to its logical limits, then there is no market mechanism and all impediments related to the central planning system disappear. This interpretation is in line with the Hayekian interpretation of the market as a mechanism for acquiring knowledge.